(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the role of philosophical categories in improving the moral and ethical qualities of future teachers. The study presents the results of experimental research conducted to assess the effectiveness of philosophical principles in teacher training programs. The findings demonstrate how philosophical concepts can contribute to the formation of professional ethics, responsibility, and a sense of social duty among prospective educators.